2013
DOI: 10.1021/ac303292e
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibers as Substrates for Surface-Assisted Laser Desorption/Ionization and Matrix-Enhanced Surface-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Electrospun polymeric nanofibers (polyacrylonitrile, poly(vinyl alcohol), and SU-8 photoresist) and carbon nanofibers pyrolyzed to final temperatures of 600, 800, and 900 °C were used as substrates for surface-assisted laser desorption/ionization (SALDI) and matrix-enhanced surface-assisted laser desorption/ionization (ME-SALDI) analyses. Sample preparation of polymeric analytes using the electrospun target plate for SALDI analysis is simple and fast. Signal enhancements for poly(ethylene glycol) were noted wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 62 publications
(134 reference statements)
1
24
0
2
Order By: Relevance
“…Although we could detect PEG species at all molecular weights in this range, the peak intensity of PEG 42,700 was quite low, because the ionization and desorption efficiencies of ions of relatively high molecular weight are typically low [62][63][64][65]. To the best of our knowledge, this PEG species has the highest molecular weight ever analyzed using an LDI-MS method [66].…”
Section: Analyses Of Peg Polymers Of Various Molecular Weightsmentioning
confidence: 83%
“…Although we could detect PEG species at all molecular weights in this range, the peak intensity of PEG 42,700 was quite low, because the ionization and desorption efficiencies of ions of relatively high molecular weight are typically low [62][63][64][65]. To the best of our knowledge, this PEG species has the highest molecular weight ever analyzed using an LDI-MS method [66].…”
Section: Analyses Of Peg Polymers Of Various Molecular Weightsmentioning
confidence: 83%
“…Some reviews coved application of SALDI MS technique in analysis of different classes of organic compounds . SALDI MS being performed with UTLC plates with bonded matrix sounds even more promising . Plates with nanofibrous carbon substrates and composite nanofibers (PAN/Nafion®/CNT) demonstrated minimal fragmentation and signal enhancements for poly(ethylene glycol) compared to those obtained with commercially available stainless steel plates.…”
Section: Methods Of Detection (Ldi Maldi)mentioning
confidence: 99%
“…A set of six laser dyes, as well as a mixture of three labeled amino acids: lysine, threonine, and phenylalanine, were fully resolved on the carbon UTLC plate demonstrating tunable retention and plate number values above 10 000 theoretical plates. Later, other polymeric nanofibers (polyacrylonitrile, poly(vinyl alcohol) and carbon nanofibers ) were pyrolyzed to final glassy carbon ultra‐thin layers demonstrating ability for surface‐assisted laser desorption/ionization and matrix‐enhanced surface‐assisted laser desorption/ionization analyses which are discussed in Section 3.2.…”
Section: Preparation Of Monolithic Layersmentioning
confidence: 99%
“…Due to the inherent advantages, such as unique structure, large surface area, good performance in optical properties, carbon-based nanomaterials including fullerenes [28], nanodiamond [29,30], nanofibers [31], nanohorns, nanotubes, nanodots, and graphene have been considered as a kind of good candidate matrix for LDI to analysis of small molecules since Sunner and co-workers [19] demonstrated that graphite particles with size of 2–150 µm can be served as matrix for LDI-TOF MS.…”
Section: Nanomaterial-assisted Ldi Methods Developmentmentioning
confidence: 99%